CGA G-13 large-scale silane release tests – Part I. Silane jet flame impingement tests and thermal radiation measurement. (July 2015) - Ngai, Eugene Y.; Fuhrhop, Ron; Chen, Jenq-Renn; Chao, Jenny; Bauwens, C. Regis; Mjelde, Crystal; Miller, Gary; Sameth, Jerry; Borzio, John; Telgenhoff, Michael; Wilson, Bruce
Abstract: In early 2011, the G-13 Silane Modeling Task Force of the Compressed Gas Association (CGA) proposed a series of tests to better define pyrophoric behavior during unintentional, large-scale releases of silane. The tests were conducted in two phases under the direction of CGA and its guidelines. Phase I took place from June 27 to June 30, 2011, focusing primarily on thermal radiation and the heat transfer from flame impingement due to silane release from a fully open pressure relief device (PRD) on a tonner. Phase II took place on June 19 and 20, 2012, focusing on thermal radiation and explosion overpressure. The results were subsequently utilized to revise CGA G-13 guidelines on the safe handling of silane. In the present two-part papers, the results from the tests are summarized in order to highlight the key findings. The first part of summary described the results of the flame impingement and thermal radiation tests. Three different test series were conducted, including shakedown tests using nitrogen instead of silane, silane flame-impingement tests onto an adjacent target tonner, and heat-flux tests. For comparison with known values in the published literature, thermal radiation of ethylene flame jets was also measured. In addition, metallurgical analyses of the target tonner indicated that the metallurgical properties of the cylinder material were not altered by the flame impingement. The steel surface temperature at the point of impingement was estimated to be below 853.15 K and definitely did not exceed 950.15 K. Thus, the combination of internal pressure and vessel metal temperature was unlikely to exceed the rupture pressure of the ton cylinder. Highlights: Large-scale field trials were done to evaluate the hazards of silane jet flame. The tests included jet flame impingement and thermal radiation measurement. A jet flame from a silane tonner leak will not cause a rupture of nearby tonner. Results were used to revise ANSI/CGA G-13 standard.